Sporotrichosis in Cats Caused by Sporothrix brasiliensis in Two Microregions of Brazil - Spanamberg, Andréia; Beatriz Fuentes; Ricardo Araujo; Cibele Floriano Fraga; Gisele Alabora; Priscila Sordi; Laerte Ferreiro (Acta Scientiae Veterinariae, 2025)
Background: Sporotrichosis is a subcutaneous mycosis of humans and animals. In recent years, several cities in Brazil have recorded an increase in cases due to zoonotic transmission through cats. The classic clinical presentation is transmitted through plant debris and the 2nd way (zoonotic form) is caused by animal transmission. The alternative zoonotic route has gained attention due to the rapid and significant spread of cat-transmitted sporotrichosis in South America. The aim of this work was to identify the Sporothrix species responsible of feline sporotrichosis based on reference standard and molecular methods. Cases: All isolates were recovered from skin of 27 cats with sporotrichosis between 2020 and 2024. Fifteen cats sampled were from state of Santa Catarina (microregion of Florianópolis) and, 12 from state of Rio Grande do Sul (11 from microregion of Porto Alegre / 1 from Serafina Corrêa city), Brazil. Clinical diagnosis of sporotrichosis was made through examination (inspection and palpation of skin and/or mucous lesions, palpation of superficial lymph nodes and cardiopulmonary auscultation) and cytopathology. The cytopathological examination was performed either by imprint in ulcerated lesions/swabs. Yeast-like structures were observed in cytopathological exam. Fungal growth in mycological culture (Sabouraud Cycloheximide-Chloramphenicol Agar, incubated at 25°C and 37°C for 10 to 30 days) was monitored by forming dark black colonies. Physiological tests (assimilation of sucrose and raffinose), microscopy of hyphae/conidia and macroscopic colony characteristics (colors and texture) were conducted for the identification of the species. All isolates included in the study exhibited similar macroscopic morphology in their filamentous form. Microscopic observation of the isolates showed presence of septate hyphae showing at the end of conidiophores conidia arranged in a “daisy-like” pattern (sympodial formation). Assimilation tests using sucrose and raffinose were negative. Sporothrix brasiliensis was the only agent involved in feline sporotrichosis. The identity of isolates was confirmed using specific primers for the CAL gene and sequencing analyses. Discussion: According to the literature, our result corroborates reports from other authors who describe cases of sporotrichosis caused by Sporothrix brasiliensis in several states in Brazil. Although S. brasiliensis is predominant, the identification of fungal species is essential to determine the etiology of sporotrichosis in different areas of the country, and to indicate a possible change in the current scenario of the disease. The transboundary expansion of the species occurs between states and more cases of cat-cat/cat-dog and cat-human transmission may occur; situation described in this work. In the state of Rio Grande do Sul (RS), S. brasiliensis was the only isolated species. Sporothrix brasiliensis is considered the most virulent species within pathogenic clade and represents an important not only in Brazil, but also in other South American countries; among them are the Paraguay, Argentina and Chile with a description of feline sporotrichosis. In Panama (Central America) the 1st case of zoonotic transmission was reported, however the species of Sporothrix genus was not discriminated through molecular diagnosis. In conclusion, the real situation of sporotrichosis in Brazil can be assessed through the clinical diagnosis of sporotrichosis in felines, as well as in humans that have had zoonotic transmission. In addition, laboratory diagnosis, with the respective determination of the species involved. This way the disease will become more visible and effective control measures can be taken within the scope of public health. Keywords: cats, Sporothrix brasiliensis, zoonosis, molecular methods, calmodulin, cutaneous, disseminated sporotrichosis.